Cartilage restoration of patellofemoral lesions: a systematic review - Andrade, R. (2021)
Purpose This study aimed to systematically analyze the postoperative clinical, functional, and imaging outcomes, complications, reoperations, and failures following patellofemoral cartilage restoration surgery. Methods This review was conducted according to the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). PubMed, EMBASE, and Cochrane Library databases were searched up to August 31, 2018, to identify clinical studies that assessed surgical outcomes of patellofemoral cartilage restoration surgery. The Methodological Index for Non-Randomized Studies (MINORS) was used to assess study quality. Results Forty-two studies were included comprising 1,311 knees (mean age of 33.7 years and 56% males) and 1,309 patellofemoral defects (891 patella, 254 trochlear, 95 bipolar, and 69 multiple defects, including the patella or trochlea) at a mean follow-up of 59.2 months. Restoration techniques included autologous chondrocyte implantation (56%), particulated juvenile allograft cartilage (12%), autologous matrix-induced chondrogenesis (9%), osteochondral autologous transplantation (9%), and osteochondral allograft transplantation (7%). Significant improvement in at least one score was present in almost all studies and these surpassed the minimal clinically important difference threshold. There was a weighted 19%, 35%, and 6% rate of reported complications, reoperations, and failures, respectively. Concomitant patellofemoral surgery (51% of patients) mostly did not lead to statistically different postoperative outcomes. Conclusion Numerous patellofemoral restoration techniques result in significant functional improvement with a low rate of failure. No definitive conclusions could be made to determine the best surgical technique since comparative studies on this topic are rare, and treatment choice should be made according to specific patient and defect characteristics.